The Analysis of Register Used in DOTA 2 - Novandi, Alif Brian (Language Horizon: Journal of Language Studies, 2022)
Register is a language used by a group of people who have certain common interest. Here, the register used by gamers in playing Dota are various. It can be in the form of word, phrase, or even an acronym or other word structures possible. Each form of register is used differently based on the event or the moment. There are approximately 30 data in the form of words found and analyzed in this research using qualitative method in which the data are in form of words and explained more detail through wide explanation (Hancock, Ockleford, & and Windridge, 2009, p. 7). The researcher directly participates in playing the online game, Dota 2 andstays asthe observer. This research applies direct participation and observation.As there is language contact happens during the gameplay among Dota players or gamers, the findings are classified into two: the first is the characteristics of word used in register used by Dota gamers and the second is the use of the register as an aspect of solidarity. First, the characteristics of wordchoice in registerused by Dotagamers are the use of shortterms and the changing of wordsmeaning. Second, the purpose of the use of register by Dota 2 players is as an aspect of solidarity. They use the register to show that their relationship is intimate.